1991
DOI: 10.1002/aja.1001920204
|View full text |Cite
|
Sign up to set email alerts
|

Localization of boar sperm proacrosin during spermatogenesis and during sperm maturation in the epididymis

Abstract: The localization of proacrosin was determined by using colloidal gold labeling and electron microscopy of boar germ cells during spermiogenesis to post-ejaculation. Proacrosin was first localized in round spermatids during the Golgi phase of spermiogenesis; it was associated with the electron-dense granule, or acrosomal granule that was conspicuous within the acrosome. It remained within the acrosomal granule during the cap and acrosome phases of spermiogenesis. At these stages, there was no apparent associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…At this stage, acrin1 further drastically changed its location from the peripheral to the dorsal matrix region in the apical segment. Other acrosomal proteins such as human SP-10 (Kurth et al, 1991) and boar proacrosin (Bozzola et al, 1991), and the structural protein AM50 (Westbrook-Case et al, 1995) have also been shown to be redistributed at this stage, suggesting that the remodeling of acrosome shape may be involved in the final sorting and assembly of domain-specific proteins of the acrosomal matrix. Overall, the rearrangement of acrin1 during the acrosome and maturation phases seem to be closely related to the modifications in the acrosomal structural proteins.…”
Section: Discussionmentioning
confidence: 93%
“…At this stage, acrin1 further drastically changed its location from the peripheral to the dorsal matrix region in the apical segment. Other acrosomal proteins such as human SP-10 (Kurth et al, 1991) and boar proacrosin (Bozzola et al, 1991), and the structural protein AM50 (Westbrook-Case et al, 1995) have also been shown to be redistributed at this stage, suggesting that the remodeling of acrosome shape may be involved in the final sorting and assembly of domain-specific proteins of the acrosomal matrix. Overall, the rearrangement of acrin1 during the acrosome and maturation phases seem to be closely related to the modifications in the acrosomal structural proteins.…”
Section: Discussionmentioning
confidence: 93%
“…The next day the samples were transferred into the same rinse buffer containing 0.1 M glycine. The ultrathin sections were prepared from LR White-embedded tissue and used to perform colloidal gold labeling as described (20).…”
Section: Flag-mentioning
confidence: 99%
“…Several intra-acrosomal proteins exhibit modifications of the molecular weights during epididymal maturation. For example, proacrosin of boar spermatozoa appears to be localized on the IAM and OAM as well as in the acrosomal matrix (Bozzola et al, 1991). Molecular size reduction is reported in the spermatozoa of rabbit (Mukerji and Meizel, 1979), boar (Baba et al, 1989), guinea pig (Anakwe et al, 1991), rat (NagDas et al, 1992), and human (Baba et al, 1994).…”
Section: Acrosomal Modifications Duringmentioning
confidence: 93%
“…In these stages, acrosomal proteins are generally transported from the endoplasmic reticulum into the developing acrosomal system through the Golgi apparatus until the end of the cap phase (Clermont and Tang, 1985). For example, boar proacrosin (Bozzola et al, 1991), guinea pig AM 50 (Westbrook-Case et al, 1995), rat and guinea pig acrin1 (Tanii et al, 1994;Yoshinaga et al, 2000), and mouse sp56 (Kim et al, 2001a) first appear in association with Golgi-derived granules and the developing acrosomal vesicle of early spermatids (Fig. 2a).…”
Section: Acrosomal Organization Duringmentioning
confidence: 96%
See 1 more Smart Citation